Effect of a baby‐friendly workplace support intervention on exclusive breastfeeding in Kenya - Elizabeth W. Kimani‐Murage; Calistus Wilunda; Teresia Njoki Macharia; Eva Watiri Kamande; Peter Muriuki Gatheru; Tadesse Zerfu; Hermann Pythagore Pierre Donfouet; Laura Kiige; Susan Jabando; Lynette Aoko Dinga; Betty Samburu; Richard Lilford; et al. (Wiley, 2021)
Abstract Exclusive breastfeeding (EBF) during the first 6 months of life is crucial for optimizing child growth, development and survival, as well as the mother's wellbeing. Mother's employment may hinder optimal breastfeeding, especially in the first 6 months. We assessed the effectiveness of a baby‐friendly workplace support intervention on EBF in Kenya. This pre‐post intervention study was conducted between 2016 and 2018 on an agricultural farm in Kericho County. The intervention targeted pregnant/breastfeeding women residing on the farm and consisted of workplace support policies and programme interventions including providing breastfeeding flexi‐time and breaks for breastfeeding mothers; day‐care centres (crèches) for babies near the workplace and lactation centres with facilities for breast milk expression and storage at the crèches; creating awareness on available workplace support for breastfeeding policies; and home‐based nutritional counselling for pregnant and breastfeeding women. EBF was measured through 24‐h recall. The effect of the intervention on EBF was estimated using propensity score weighting. The study included 270 and 146 mother-child dyads in the nontreated (preintervention) group and treated (intervention) group, respectively. The prevalence of EBF was higher in the treated group (80.8%) than in the nontreated group (20.2%); corresponding to a fourfold increased probability of EBF [risk ratio (RR) 3.90; 95% confidence interval (CI) 2.95-5.15]. The effect of the intervention was stronger among children aged 3-5 months (RR 8.13; 95% CI 4.23-15.64) than among those aged <3 months (RR 2.79; 95% CI 2.09-3.73). The baby‐friendly workplace support intervention promoted EBF especially beyond 3 months in this setting.